2021
DOI: 10.3389/fphys.2020.624625
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Effect of Fetal Mesenchymal Stem Cells in the Mother–Fetus Dyad in COVID-19 Pregnancies and Vertical Transmission?

Abstract: Because of the polysystemic nature of coronavirus disease 2019 (COVID-19), during the present pandemic, there have been serious concerns regarding pregnancy, vertical transmission, and intrapartum risk. The majority of pregnant patients with COVID-19 infection present with mild or asymptomatic course of the disease. Some cases were hospitalized, and few needed intensive care unit admission, or mechanical ventilation. There have also been scarce case reports where neonates required mechanical ventilation post C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 163 publications
(91 reference statements)
0
6
0
1
Order By: Relevance
“…There anti-inflammatory actions are mediated by modulating Treg cells and macrophages as well as alleviating cytokines proliferation [ 32 ]. They attenuate the recruitment of macrophages and mononuclear cells to the lungs together with increased IL10 levels [ 18 ]. The MSCs stimulate the transition of the inflammatory macrophage phenotype M1 to the anti-inflammatory and wound-healing M2 phenotype [ 34 ].…”
Section: Anti-inflammatory Immunomodulatory and Antiviral Roles Of Th...mentioning
confidence: 99%
See 2 more Smart Citations
“…There anti-inflammatory actions are mediated by modulating Treg cells and macrophages as well as alleviating cytokines proliferation [ 32 ]. They attenuate the recruitment of macrophages and mononuclear cells to the lungs together with increased IL10 levels [ 18 ]. The MSCs stimulate the transition of the inflammatory macrophage phenotype M1 to the anti-inflammatory and wound-healing M2 phenotype [ 34 ].…”
Section: Anti-inflammatory Immunomodulatory and Antiviral Roles Of Th...mentioning
confidence: 99%
“…The latter reported that pregnant women have higher risk of dying, being admitted to an intensive care unit, needing invasive ventilation and needing extracorporeal membrane oxygenation than non-pregnant women [ 43 ]. Thus far, the prevalence of neonatal COVID-19 positivity did not exceed the 5% [ 18 ]. It is interesting to note that in the majority of COVID-19-pregnancy instances, SARS-CoV-2 mother-to-fetus transmission has not been identified which might be due to the presence of lactoferrin in the placenta, amniotic fluid and lacteal secretions.…”
Section: Covid-19 Infection In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha reportado títulos elevados de IgM contra el SARS-CoV-2 en un recién nacido. Como la IgM no se puede transferir a través de la placenta y solo puede ser producida por el feto en respuesta al virus, este resultado y las lesiones hepáticas del recién nacido sugieren indirectamente la posibilidad de transmisión vertical (84).…”
Section: Transmisión Verticalunclassified
“…The fetal cells that transfer through the placenta are from specific cell types, including hematopoietic stem cells and MSCs [93]. Samara et al recently suggested that fetal MSCs circulating in the maternal blood may have an immunosuppressive effect on mothers, causing COVID-19 in pregnant women to be often mild and even asymptomatic [94]. Pietras et al have neatly characterized the cell cycle regulation in hematopoietic stem cells from fetal, adult, and aged sources.…”
Section: Active Versus Quiescent Stem Cellsmentioning
confidence: 99%